1993
DOI: 10.1038/bjc.1993.432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of EGF-receptor in papillary thyroid carcinoma

Abstract: Summary In this study of papillary thyroid carcinomas, immunopositivity for EGF-receptor was present in a majority of the cases (96%), although different staining patterns were observed. A distinct membraneous reaction was found in 46%, whereas cytoplasmatic positivity of various degrees was present in 90% of the cases. Strong cytoplasmic EGF-receptor staining was significantly associated with extra-thyroidal growth of the primary tumour (P = 0.009), and it was furthermore related to decreased recurrence free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 32 publications
6
32
0
Order By: Relevance
“…Numerous studies have reported that the overexpression of EGFR in an anaplastic, undifferentiated subtype of PTC is associated with a high mortality rate (28)(29)(30)(31). However, little is known about the value of EGFR expression in predicting the prognosis of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that the overexpression of EGFR in an anaplastic, undifferentiated subtype of PTC is associated with a high mortality rate (28)(29)(30)(31). However, little is known about the value of EGFR expression in predicting the prognosis of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Mizukami et al 27 reported a significant association between EGFR expression and PTC recurrence. Akslen et al [28][29][30] demonstrated that EGFR expression is a significant and independent prognostic factor in PTC. In multivariate analysis, cytoplasmic EGFR expression showed a significant correlation with tumour infiltration in surrounding thyroid tissue and recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…24 Many studies have reported the overexpression of EGFR in an anaplastic, undifferentiated subtype of PTC that is associated with a high mortality rate. [25][26][27][28] However, little is known about the value of EGFR expression in predicting the prognosis of thyroid carcinoma. Mizukami et al 27 reported a significant association between EGFR expression and PTC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of EGFR appears to be a negative prognostic factor in many types of tumors, but few studies have examined its prognostic role in thyroid cancers (Mizukami et al, 1991). Strong EGFR staining in papillary thyroid cancer was associated with poor prognosis (Akslen et al, 1993). These findings suggest that inhibition of EGFR may have anti-cancer efficacy in ATC.…”
Section: Anti-egfr Agentsmentioning
confidence: 99%